College physics - Serway, Raymond A (Thomson-Brooks/Cole, 2006)
COLLEGE PHYSICS provides students with a clear and logical presentation of the basic concepts and principles of physics. The authors include a broad range of contemporary applications to motivate students understanding of how physics works in the real world. In addition, new pedagogy, reflecting the findings of physics education research, has been added to help students improve their problem solving skills and conceptual understanding. The text's flexible, accessible, and focused presentation, coupled with extraordinary text/media integration through PhysicsNow, gives instructors and students the tools they need to succeed.